Research in the social scientific study of religion / Volume 18 - Piedmont, Ralph L. (Research in the Social Scientific Study of Religion Ser, 2007)
Contains various articles on spiritual development among adolescents, spiritual transcendence, Jung and pastoral counseling and spirituality and religiosity. This book also includes a section of nine articles which is devoted to several aspects of positive psychology and its usage in practice